Idea of apostolic succession in the epistle of St. Firmilian of Caesarea to St. Cyprian of Carthage - Georgy Zakharov (Вестник Православного Свято-Тихоновского гуманитарного университета: Серия I. Богословие, философия, 2019)
This article analyses St. Firmilian’s of Caesarea doctrine of apostolic succession, formulated in his letter to Cyprian of Carthage (256). This text was written in connection with the disagreements as to the necessity for the baptism of heretics who converted to Catholic faith. St. Firmilian and St. Cyprian regarded heretical baptism as invalid, whereas the Roman bishop Stephen referred to the local Roman tradition, which seemingly went back to the apostles. He also referred to his own authority as apostle Peter’s successor and insisted on rejecting the practice of repeated baptism of heretics. In this controversy, questions were raised about the status of apostle Peter as the foundation for ecclesiastic unity, about the successive transmission of apostolic testimony in local churches and their hiararchy of authority, as well as about the transmission of the power to absolve of sins from the apostles to bishops. As the author of the article tries to show, St. Firmilian largely adopts the universalist ecclesiology of St. Cyprian, but at the same time complements his argumentation with reasons based on the earlier local and historical interpretation of the apostolic succession typical of Hegesippus, St. Irenaeus of Lyon, and Tertullian. In particular, St. Firmilian contrasts the Roman tradition with the authority of Jerusalem Church and claims that the customs of the Church of Caesarea are of the apostolic origin. A prominent place in St. Firmilian’s epistle is occupied by a polemic against Montanists. Particular emphasis on the transfer of episcopal power through the ordination anticipates in the doctrine of St. Firmilian the formation of a system of ecclesiastical provinces in the East, within which the control over the episcopal ordinations is concentrated in hands of the metropolitan. Within the framework of such a system of church organisation, the apostolic succession begins to be viewed not as something belonging to the local Church, but as a gift given to it from the outside by bishops’ college. The ecclesiological problems of the controversy over the baptism of heretics seem topical in the light of the current crisis in relations between local Orthodox Churches.